The status of distance learning during the Corona pandemic from the point of view of higher education faculty members "Dubai as a model" - Merdas, Iman Camil (Journal of Educational and Psychological Sciences, 2022)
This research aims to identify the status of distance learning in light of the Corona pandemic from the point of view of educational faculty members, and the challenges they faced despite the availability of the technical structure required for the educational system. To achieve the goal of the research and address the problem, the qualitative approach was employed, and focus groups depended on a deliberate sample of selected faculty members (14 university professors) chosen according to their specializations in order to extract and analyze views, and obtain collective perceptions on the subject. The research concluded that the teaching staff suffered from additional time requirement for distance learning, an increase in office hours, and the lack of educational programs designed for this type of education. Moreover, the educational goals were pre-drawn, which made it challenging to achieve during the application of distance learning, in addition to the lack of technical skills needed by faculty members. Accordingly, the researcher suggested some recommendations that included: Creating an electronic platform through which faculty members can share their ideas and suggestions on developing educational technology, improving the quality of curricula and creating advanced educational content in Arabic language, designing comprehensive websites for online educational resources, and establishing free educational courses that can be accessed via the Internet.